2018
DOI: 10.1121/1.5023686
|View full text |Cite
|
Sign up to set email alerts
|

Temporal weights in the perception of sound intensity: Effects of sound duration and number of temporal segments

Abstract: Loudness is a fundamental aspect of auditory perception that is closely related to the physical level of the sound. However, it has been demonstrated that, in contrast to a sound level meter, human listeners do not weight all temporal segments of a sound equally. Instead, the beginning of a sound is more important for loudness estimation than later temporal portions. The present study investigates the mechanism underlying this primacy effect by varying the number of equal-duration temporal segments (5 and 20) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 41 publications
(79 reference statements)
4
22
0
Order By: Relevance
“…To estimate temporal loudness weights, we used an established experimental paradigm from previous experiments (e.g., [7,10,11]). The target stimuli were level-fluctuating narrowband noises consisting of ten contiguous temporal segments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate temporal loudness weights, we used an established experimental paradigm from previous experiments (e.g., [7,10,11]). The target stimuli were level-fluctuating narrowband noises consisting of ten contiguous temporal segments.…”
Section: Methodsmentioning
confidence: 99%
“…One reason may be that not all temporal parts of a sound are weighted equally when listeners judge loudness. Previous studies consistently show that the beginning of a time-varying sound is of higher importance for the perception of loudness than later temporal parts [79], which has been referred to as a primacy effect (for a review see [10]). The primacy effect can be described by an exponential decay function with a time-constant of about 200–300 ms [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should systematically compare this seemingly divergent pattern of aberrant weighting of prediction errors during early sensory perception versus behavior at higher levels of information-processing (for example by investigating different types of primacy biases, e.g. Bronfman et al, 2016;Kotchoubey, 2014;Oberfeld et al, 2018). Another interesting research direction might be to formalize these observations and theories in a computational model of, for example, trial-by-trial MMN responses (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive and memory effects have been more widely explored in studies of temporal weighting of loudness, where the initial and final segments of a sound are generally found to receive greater weight (Dittrich and Oberfeld, 2009;Oberfeld, 2009Oberfeld, , 2015Oberfeld and Plank, 2011;Oberfeld et al, 2018;Pedersen and Ellermeier, 2008;Rennies and Verhey, 2009). Pedersen and Ellermeier (2008) found that correct-answer feedback led to a reduction in the weight assigned to the initial and final segments, a shift to more optimum temporal weights.…”
Section: Discussionmentioning
confidence: 99%